Kawasaki Disease in a 3-Month-Old Infant: How to Remain Vigilant?. Issue 12 (December 2019) - Nguyen, Thanh; M'Buila, Celestin; Bui van, Tung; Barat, Maxime; Loire, Mathilde
Abstract : Background: Kawasaki disease is an acute vasculitis occurring between 6 months and 5 years old. Patients younger than 6 months have mostly incomplete form. This clinical symptoms lead to confusion and delayed diagnosis. Case Report: We developed the diagnostic difficulties with a 3-month-old infant. At the beginning, his incomplete presentation misled pediatricians. Conclusions: We highlight the possibilities of Kawasaki disease in infants younger than 6 months. Indeed, every diagnostic delay increases cardiovascular risk. Nonetheless, in our case, treatment was prescribed in the first 5 days, and the patient developed aneurysms.